Financial liberalisation and international market interdependence: evidence from China’s stock market in the post-WTO accession period - He, Hongbo; Chen, Shou; Yao, Shujie; Ou, Jinghua (Elsevier, 2014)
This paper studies China’s stock market with respect to financial liberalization and international market interdependence after its accession to the WTO in 2001. Using the multi-factor R-squared measure, we derive a normalized index to measure the impact of financial liberalization policies on stock market interdependence between China and the world. Some of China’s financial liberalization measures, such as QFII and exchange rate reform, are found to have played an important role in increasing market interdependence. After the US credit crunch in 2007 and the world financial crisis in the following years, some anomalies were observed as China’s stock market was more interdependent of the global market than the US stock market in some specific periods. These anomalies may have been related to the former’s overreaction and economic overheating.